2013
DOI: 10.1590/s0103-50532013000300013
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric corrosion of galvanized steel and precipitation runoff from zinc in a marine environment

Abstract: Este estudo focaliza o comportamento do aço galvanizado em um ambiente marinho corrosivo e no processo de escoamento superficial para o mesmo material que ocorrem em Valparaíso, Chile. O potencial de corrosão e a taxa de corrosão avaliados através de perda de massa foram utilizados para determinar os danos da corrosão para o aço galvanizado. As composições dos produtos de corrosão foram determinadas utilizando difratometria de raios X (XRD) e sua morfologia através da microscopia eletrônica de varredura (SEM).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 20 publications
(26 reference statements)
2
6
1
Order By: Relevance
“…Results obtained from the current study are in agreement with the findings of Syed et al and Volovitch et al Findings are also consistent with the results reported by Vera, et al and Natesan et al…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Results obtained from the current study are in agreement with the findings of Syed et al and Volovitch et al Findings are also consistent with the results reported by Vera, et al and Natesan et al…”
Section: Resultssupporting
confidence: 93%
“…This could be due to higher humidity and closeness to the sea. [13] Results obtained from the current study are in agreement with the findings of Syed et al [2,4] and Volovitch et al [32] Findings are also consistent with the results reported by Vera, et al [24,33] and Natesan et al [23,[25][26]…”
Section: Electrogalvanized Mild Steelsupporting
confidence: 92%
See 3 more Smart Citations